2012
DOI: 10.1080/09589236.2012.661594
|View full text |Cite
|
Sign up to set email alerts
|

The discursive construction of ‘bounded masculinity/unbounded femininity’

Abstract: The end of World War II saw the emergence of a gendered division of labour in Japan where 'salarymen' committed themselves to their workplaces, while 'professional housewives' devoted themselves to domestic work and childcare. Masculinity can therefore be seen as 'bounded' since social norms constructed men as family breadwinners. On the other hand, femininity can be seen as 'unbounded' in that women were released from the pressure to assume a breadwinning role. This article draws on critical discursive psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, fathers seem to ultimately prioritise the provider role and continue to organise their caregiving responsibilities around the demands of their workplaces (Braun, Vincent, & Ball, 2011;Gatrell, Burnett, Cooper, & Sparrow, 2015). Prioritising employment is connected to notions of fathers as ideal workers (Holter, 2001), to structural constraints and attitudes (Steiber & Haas, 2010) and to ideals of masculinity (Charlebois, 2012;Holter, 2007;Schmidt, Rieder, Zartler, Schadler, & Richter, 2015). Fathers seem to be required to develop fatherhood identities separately from the traditional male breadwinning identity (Höfner, Schadler, & Richter, 2011;Larsson & Björk, 2017).…”
Section: What Is Breadwinning?mentioning
confidence: 99%
“…However, fathers seem to ultimately prioritise the provider role and continue to organise their caregiving responsibilities around the demands of their workplaces (Braun, Vincent, & Ball, 2011;Gatrell, Burnett, Cooper, & Sparrow, 2015). Prioritising employment is connected to notions of fathers as ideal workers (Holter, 2001), to structural constraints and attitudes (Steiber & Haas, 2010) and to ideals of masculinity (Charlebois, 2012;Holter, 2007;Schmidt, Rieder, Zartler, Schadler, & Richter, 2015). Fathers seem to be required to develop fatherhood identities separately from the traditional male breadwinning identity (Höfner, Schadler, & Richter, 2011;Larsson & Björk, 2017).…”
Section: What Is Breadwinning?mentioning
confidence: 99%
“…Finally, our analysis of disabled men’s emotions also revealed that in light of disablism, men resisted and rejected dominant notions of masculinity and formulated affirmative masculinities consistent and accepting of the limitations of stuttering. Charlebois (2012) argued individuals have the ability to resist dominant ideologies, which is a crucial step towards changing the existing hegemonic gender order. Marginal men, similar to, men who stutter, may well play a role at the forefront of change.…”
Section: Discussionmentioning
confidence: 99%
“…US culture maintains a “Good Mother Ideal” of intensive mothering, child‐focused living, long‐term breastfeeding, and other lifestyle features that are difficult for a fully employed parent to maintain. As Charlebois notes, a “full‐time homemaker is a culturally dominant image of hegemonic femininity” (2010, p. 45). When the Good Mother Ideal is not reached, working mothers often feel substantial guilt.…”
Section: Sociolegal Scholarship Related To Lactation At Workmentioning
confidence: 99%